Mothers in Eastern and Western Germany: Employment rates and attitudes are converging, full-time employment is not - Denise Barth; Jonas Jessen; C. Katharina Spieß; Katharina Wrohlich (DIW Weekly Report, 2020)
Work and family life arrangements differed greatly between the east and west before German reunification in 1990. Since reunification, however, the employment rates of mothers with children requiring childcare have converged. This trend is accompanied by a growing approval of maternal employment, especially in western Germany. However, differences in actual working hours remain. Mothers in the east work full time markedly more often compared to mothers in the west. However, women in younger age cohorts approve less of working mother with toddlers compared to women in older age cohorts, especially in the east. It remains to be seen whether a further expansion of day care in childcare centers and elementary schools will lead to a change in attitudes and thus also in the full-time employment of mothers with young children.
Keywords: J21; J16; Z13; 330; female labor force participation; German reunification; family policy; gender roles